EFEKTIVITAS PEMBERIAN SURAT IZIN MENGEMUDI (SIM) BAGI PENYANDANG DISABILITAS DI WILAYAH HUKUM POLRESTA DENPASAR - NI PUTU NONI SUHARYANTI; ANAK AGUNG PUTU WIWIK SUGIANTARI; NI WAYAN TRISDA CITRA LAKSMI (GANEC SWARA, 2021)
Denpasar as one of the cities that has a very dense population activity, so that it has a very vulnerable impact on the movement of community activities on the highway. In an effort to control the activities of the community, it is necessary to impose restrictions through administrative arrangements in the form of requirements in an effort to drive activities for the people of Denpasar, including for persons with disabilities. Persons with disabilities are people who have physical limitations, so that in obtaining their rights, it is necessary to obtain special procedures and conditions including obtaining authentic evidence of driving in the form of a driving license which in this case for persons with disabilities obtain a SIM D. The method used in this study uses the method empirical legal research that examines the phenomenon of dass sollen and dass sein, settings and realities in society obtained through data that is processed and analyzed using qualitative methods presented in a qualitative descriptive manner. From the results of this study, it was found that the provision of SIM D at the Denpasar City Police was not effective because there were still obstacles that arose in the implementation of the service process for providing SIM D. So, Denpasar City Police should immediately make improvements both internally and externally by increasing knowledge and understanding of the implementation of the SIM D granting process as well as preparation of sapras and socialization to the communityDenpasar as one of the cities that has a very dense population activity, so that it has a very vulnerable impact on the movement of community activities on the highway. In an effort to control the activities of the community, it is necessary to impose restrictions through administrative arrangements in the form of requirements in an effort to drive activities for the people of Denpasar, including for persons with disabilities. Persons with disabilities are people who have physical limitations, so that in obtaining their rights, it is necessary to obtain special procedures and conditions including obtaining authentic evidence of driving in the form of a driving license which in this case for persons with disabilities obtain a SIM D. The method used in this study uses the method empirical legal research that examines the phenomenon of dass sollen and dass sein, settings and realities in society obtained through data that is processed and analyzed using qualitative methods presented in a qualitative descriptive manner. From the results of this study, it was found that the provision of SIM D at the Denpasar City Police was not effective because there were still obstacles that arose in the implementation of the service process for providing SIM D. So, Denpasar City Police should immediately make improvements both internally and externally by increasing knowledge and understanding of the implementation of the SIM D granting process as well as preparation of sapras and socialization to the community.